Deciphering the metabolic landscape of colorectal cancer through the lens of AhR-mediated intestinal inflammation - Swain, Jasmine; Preeti; Mohanty, Chandana; Bajoria, Atul Anand; Patnaik, Srinivas; Gahlawat, Aoife Ward; Nikhil, Kumar; Mohapatra, Soumya Ranjan (Discover oncology, 2025)
Colorectal cancer (CRC) ranks as the third most common cancer worldwide, with its incidence steadily increasing due to an aging demographic and various lifestyle-related risk factors, including poor nutrition, tobacco use, sedentary behaviour and obesity. These factors promote the risk of colorectal cancer by inducing chronic colonic inflammation, a principal catalyst of carcinogenesis. This review delves into evidence that suggests that metabolic abnormalities mediated through inflammatory responses are fundamental in the progression of CRC. This dysregulation of essential metabolic pathways in colorectal cancer, facilitates tumor proliferation, immune evasion, and metastasis. Additionally, this review explores how inflammatory mediators, and dietary carcinogens induce metabolic alterations, fostering a pro-tumorigenic milieu. Special focus is placed on the aryl hydrocarbon receptor (AhR) as a pivotal metabolic regulator that links inflammation and tumor metabolism, elucidating its function in the reconfiguration of cellular energetics and the inflammatory microenvironment. Furthermore, this review also focuses on clarifying the relationship between inflammation, metabolic dysregulation, and the progression of CRC, so as to identify potential therapeutic targets.
Gesehen am 26.08.2025